Hoffenthal, eine Anzahl Schoner im Hafen : [19--] - Bohlmann, Ernst, 1864-1945. (2001)
Photograph of Hopedale from a hill behind the mission station. Twelve fishing schooners can be seen anchored in the harbour. Photograph of Hopedale from a hill behind the mission station. Twelve fishing schooners can be seen anchored in the harbour.